The influence of achievement motivation on teacher performance at SDN in Korsatpen Banyumanik Semarang City by making career satisfaction a mediating variable. - Unik Herniati; Endi Rochaendi; Yusinta Dwi Ariyani; Saepul Ma'mun (Literasi: Jurnal Ilmu Pendidikan, 2023)
This research study aimed to examine the influence of achievement motivation on teacher performance at SDN in Korsatpen Banyumanik Semarang City by making career satisfaction a mediating variable. This research study utilized all PNS teachers at the SDN in the Korsatpen area as a population. For the research study, only 60.17 per cent were taken as a sample of a total of 231 teachers. The research method uses a descriptive approach by applying explanatory research. The study results showed that achievement motivation and teacher competence substantially influence elementary school teachers' performance in the Banyumanik Korsatpen, Semarang, which is mediated by career satisfaction. In this context, career satisfaction is a teacher's perception, mindset and behaviour that can indirectly affect performance achievement. In this connection, career satisfaction will focus on the characteristics of a teacher, which can help the teacher produce good performance on the main tasks and functions for which they are responsible. Ultimately, career satisfaction can function as attraction, retention and development indirectly from achievement motivation and teacher competence to improve teacher performance.Keywords: Achievement Motivation, Competence, Career Satisfaction, Teacher Performance.